Optimizing Marketing Strategies and Brand Image with SOSTAC: A Study of ZETTAMIND STUDIOS - Jupriyatmoko Jupriyatmoko; Tussi Sulistyowati; Nur Elfi Husda (Universitas Internasional Batam, 2024)
This research utilizes the SOSTAC methodology to tackle Zettamind Studios' social media challenges. Beginning with Situation Analysis, it decodes the current landscape through meticulous customer and competitor scrutiny. Framed within the 5S framework, the objectives aim at cinema-goers, IMDb ratings, and post-film social media growth. Strategy emphasizes nationwide cinema distribution, influencer collaborations, and service planning. Tactics deploy flexible, short-term goals in digital marketing. The comprehensive SOSTAC strategy ensures a targeted social media presence, aligning with audience preferences. The findings provide actionable insights, and recommendations guide Zettamind Studios toward a more impactful and adaptive digital presence.